Loss of Cells in the Retinal Ganglion Cell Layer as an Early Indication of Neurodegeneration in Multiple Sclerosis - Nidhi Shenoy; Fang Liu; S. Priya Narayanan (Journal of Integrative Neuroscience, 2024)
Background: Multiple Sclerosis (MS) is a debilitating neurological disease affecting the central nervous system and significantly impacting patients’ quality of life. MS is known as an autoimmune disease affecting the white matter. The disease involves inflammation, demyelination, and neurodegeneration, causing irreversible disabilities. Current treatments for MS target the inflammatory phase, with limited effects on long-term disability. While neuronal damage significantly contributes to MS pathology, mechanisms of neurodegeneration are not well studied. Methods: This study evaluated neurodegenerative changes in the retina during disease progression, using data collected from an experimental MS model (Experimental Autoimmune Encephalomyelitis, EAE). Utilizing Hematoxylin and Eosin-stained retinal sections and assessment using Optical Coherence Tomography (OCT), the study investigated the neurodegenerative changes, such as loss of cells in the retinal ganglion cell layer (GCL) and retinal thinning in the retina of the EAE model and the control groups. Results: Our results showed a significant reduction in the number of cells in the GCL of the EAE retina at two different time points studied, suggesting loss of neurons compared to the control group. Thickness measurements showed a reduction in the total retina and inner retinal layer thicknesses in the EAE retina compared to the controls. Our results indicate evidence of neurodegenerative changes in the retina of the experimental model of MS. No significant differences were observed between the percent losses of cells between the two time points studied. The pattern of cell loss suggests that neurodegeneration occurs at an earlier stage of disease progression. Conclusions: Overall, the retina is an excellent model to investigate neurodegeneration in MS, and possibly, loss of cells in the GCL could be used as an early indicator of neurodegeneration in MS and to identify novel therapeutic agents to treat the disease.